After-mission, beyond Evangelicalism: the indigenous 'Injīliyyūn' in the Arab-Muslim context of Syria-Lebanon - Awad, Najib George (Theology and mission in world christianity, 2021)
"After-Mission touches on on three questions.The first question is about self-perception and identity-formation strategies, and the various views that we have on the Protestants' relation to their Arab Muslim Middle Eastern context. This will furnish the basis for the ensuing parts, as it will provide the study with coherent and analytical readings of the cultural situation and intellectual views of the Arab Eastern Protestants in their Sitz im Leben from the perspective of the hermeneutic tripod of 'identity-othering-relationality'. The second question, about the theological dimension, asks what kind of a theological discourse do the Protestants need to develop, and how do they need to re-form their own theological heritage, in such a manner that will allow them to heal the historical enmity and suspicion towards them from the Eastern Orthodox Christian community in the region? How should they re-think their traditional view on theological subjects common to them and the Eastern Christian tradition? Traditional Protestant attitudes towards Eastern Christianity, which have been viewed through the lens of evangelicalism and mission, have failed to grant the Protestants an influential and truly indigenous presence in the region and have led to them being constantly accused of being a foreign transplant and alien entity. In the light of this, it is clear that going beyond missiology and traditional evangelicalism demands re-thinking certain mutually shared but contentious theological subjects from a new perspective with the focus on more constructive attempts to build fellowship through dialogue. Finally, the third question touches on the Protestants' future in the Arab Muslim Middle East by viewing this inquiry from a broader perspective that is related to all the Middle Eastern Christian communities' presence and role in the Muslim-majority context. It will discuss questions about the kind of presence and role that Christians, Protestants included, should hope to play in order to guarantee survival and a continuing presence in the region. The question of identity formation, and the managing of difference without trapping it in the mud of 'otherizing and self-otherizing', will also be tackled, so that the theological dimension is integrated with the broader, multifaceted contextual one"--